TRIS buffer in simulated body fluid distorts the assessment of glass-ceramic scaffold bioactivity - Rohanová, Dana; Boccaccini, Aldo Roberto; Yunos, Darmawati Mohamad; Horkavcová, Diana; Březovská, Iva; Helebrant, Aleš (Acta biomaterialia, 2011)
The paper deals with the characterisation of the bioactive phenomena of glass-ceramic scaffold derived from Bioglass® (containing 77 wt.% of crystalline phases Na(2)O·2CaO·3SiO(2) and CaO·SiO(2) and 23 wt.% of residual glass phase) using simulated body fluid (SBF) buffered with tris-(hydroxymethyl) aminomethane (TRIS). A significant effect of the TRIS buffer on glass-ceramic scaffold dissolution in SBF was detected. To better understand the influence of the buffer, the glass-ceramic scaffold was exposed to a series of in vitro tests using different media as follows: (i) a fresh liquid flow of SBF containing tris (hydroxymethyl) aminomethane; (ii) SBF solution without TRIS buffer; (iii) TRIS buffer alone; and (iv) demineralised water. The in vitro tests were provided under static and dynamic arrangements. SBF buffered with TRIS dissolved both the crystalline and residual glass phases of the scaffold and a crystalline form of hydroxyapatite (HAp) developed on the scaffold surface. In contrast, when TRIS buffer was not present in the solutions only the residual glassy phase dissolved and an amorphous calcium phosphate (Ca-P) phase formed on the scaffold surface. It was confirmed that the TRIS buffer primarily dissolved the crystalline phase of the glass-ceramic, doubled the dissolving rate of the scaffold and moreover supported the formation of crystalline HAp. This significant effect of the buffer TRIS on bioactive glass-ceramic scaffold degradation in SBF has not been demonstrated previously and should be considered when analysing the results of SBF immersion bioactivity tests of such systems.
Keywords: Body Fluids; sklo; Biocompatible Materials; Spectrophotometry, Atomic; biokompatibilní materiály; tělesné tekutiny; Microscopy, Electron, Scanning; Powder Diffraction; Glass; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Ceramics; Tromethamine; keramika; mikroskopie elektronová rastrovací; prášková difrakce; spektrofotometrie atomová; tromethamin